การประเมินความต้องการจำเป็นในการจัดการชั้นเรียนที่เน้นความแตกต่างระหว่างบุคคล ของนิสิตนักศึกษาครู - เจริญพร เชี่ยวเวทย์; แกมเกตุ วรรณี (An Online Journal of Education, 2018)
The objectives of this research were 1) to analyze the knowledge and the understanding of preservice teachers’ differentiated classroom management, 2) to prioritize needs of preservice teachers’ differentiated classroom management. The participants were 724 preservice teachers. Research instruments employed to collect the quantitative data included a questionnaire of preservice teachers’ differentiated classroom management by researcher. Quantitative data was analyzed using percentage and modified priority needs index (PNImodified) The research findings were as follows; 1) the mean scores of the knowledge and the understanding of preservice teachers university A was at 4.93 (54.80%), standard deviation was at 1.82, while the mean scores of knowledge, understanding of preservice teachers university B was at 3.69 (41.00%), standard deviation was at 1.75 2) the preservice teachers are lack of the knowledge of dimension on making instruments and student assessment decision including how to assign worksheet in differentiated classroom. Moreover, the preservice teachers should know the students’ background knowledge so that they can prepare the lesson plan before teaching.